Transforming the Future Anticipation in the 21st Century - Miller, Riel (Taylor & Francis, 2018)
People are using the future to search for better ways to achieve sustainability, inclusiveness, prosperity, well-being and peace. In addition, the way the future is understood and used is changing in almost all domains, from social science to daily life. This book presents the results of significant research undertaken by UNESCO with a number of partners to detect and define the theory and practice of anticipation around the world today. It uses the concept of 'Futures Literacy' as a tool to define the understanding of anticipatory systems and processes - also known as the Discipline of Anticipation. This innovative title explores: •• new topics such as Futures Literacy and the Discipline of Anticipation; •• the evidence collected from over 30 Futures Literacy Laboratories and presented in 14 full case studies; •• the need and opportunity for significant innovation in human decision-making systems. This book will be of great interest to scholars, researchers, policy-makers and students, as well as activists working on sustainability issues and innovation, future studies and anticipation studies.